The Impact of Using English as the Medium of Instruction in Teaching Reading - Dewi Yani (Universitas Serambi Mekkah, 2022)
The language that is used in teaching influences the success of teaching and learning process. When the medium used by teachers in teaching and learning process is not effective; thus, it makes the students get problem in learning English, including in learning reading skill. The aim of the study is to find out if the usage of English as the medium of language instruction in teaching students’ reading skill is better than the common way, and to find out how the students respond toward English as the medium of instruction during learning reading. This study is conducted by using one group pre-test and post-test design. The total population of this study was 60 students in the second grade (class VIII1 and class VIII2). While the sample of this study is students who are taken from class VIII1. The researcher used purposive sampling technique in choosing sample. The data were collected through test and questionnaire. The data were then analyzed by using t-test and percentage. The result of t-test calculation shows that t-test (8.34) is higher than the critical value of t-test for the degree freedom of 29, which is 1.70 at the level of significance 0.05. It means that the usage of English as the medium of language instruction in teaching students’ reading skill is better than the conventional language instruction. Based on the result of the study, the English teachers are suggested to use English as the medium of language instruction in teaching the students’ reading skill because it can increase the students' ability in mastering reading skill.